Family counseling as assistance in solving family life problems - Gałęska, Urszula (Karkonoska Państwowa Szkoła Wyższa, 2011)
Theoreticians and practitioners of family counseling are carefully observing, analyzing and explaining a dramatically growing need for indirect help sought by problem families. The rich Internet offer of the help which is placed at the end of the article is the proof of that demand. In this situation in the of family guidance some questions are becoming especially controversial: What are the reasons for using of such a for of psychological, pedagogical legal or medical help? Is it possible that Internet advice will soon dominate or even take over the traditional help? Does the access to free and anonymous advice at any time and in any place without any barriers decide on the growing number of users. The contents of the article are a certain trial to answer the above questions.
Keywords: family; counseling; problems; help